Low-Cost Three-Quadrant Single Solar Cell I-V Tracer - José Ignacio Morales-Aragonés; Víctor Alonso Gómez; Sara Gallardo-Saavedra; Alberto Redondo-Plaza; Diego Fernández-Martínez; Luis Hernández-Callejo (Applied Sciences, 2022)
An I-V curve measurement technique is one of the most important techniques available for characterising photovoltaic cells. Measuring an accurate I-V curve at the single-cell level is a challenging task because of the low voltages and high currents implied, requiring the management of very low impedances. In this paper, the authors propose a low-cost device for I-V curve measurements of single (or small amounts) of cells in a series based on the charge transfer between two capacitors of equal capacitance. Our measurement strategy allows us to trace the usual first quadrant curve (the normal working region of solar cells) as well as the second and fourth quadrants of the I-V curve, which are quite important for research purposes. A prototype was built to demonstrate the feasibility and successful measurements of the three-quadrant I-V curve, obtained for more than 20 different cells. To use the device in a laboratory, without depending on the solar irradiation, a modular platform was 3D-printed, integrating a board with infrared LEDs as irradiating devices, and housing (to place the solar cell under test). The result is a useful low-cost setup for three-quadrant I-V curve tracing that works as expected.